Spatial clustering of HIV/AIDS mortality events in rural South Africa population between 2000-2006 - Namosha, Elias E (My University, 2010)
Background: Cluster detection analysis could be an appropriate approach to identify critical AIDS mortality locations for public health intervention. Methods: GIS and Kulldorff’s spatial scan statistic was used to investigate statistically significant AIDS mortality clusters (p 0.05). SaTScan was used to perform the spatial analysis scanning while MapInfo was used as a visualizing tool. Mortality data between 2000- 2006 were analyzed. Results: AIDS exhibit strong spatial clustering tendencies as measured by the Kulldorff’s spatial scan statistic method. Conclusion: Further work is needed to understand the underlying mechanisms responsible for the spatial clustering.
MSc (Med), Population-Based Field Epidemiology, Faculty of Health Sciences, University of the Witwatersrand, 2009
Keywords: mortality; HIV/AIDS; rural South Africa